Building Resilience through Financial Inclusion at Mercy Corps - Petryniak, Olga (2019)
Olga Petryniak Building Resilience through Financial Inclusion: A Review of Existing Evidence and Knowledge Gaps Co-Organized by IFPRI and Innovations for Poverty Action (IPA) MAY 9, 2019 - 12:15 PM TO 01:45 PM EDT